2008
DOI: 10.1074/jbc.m800163200
|View full text |Cite
|
Sign up to set email alerts
|

3-Isobutylmethylxanthine Inhibits Hepatic Urea Synthesis

Abstract: We previously showed that agmatine stimulated hepatic ureagenesis. In this study, we sought to determine whether the action of agmatine is mediated via cAMP signaling. A pilot experiment demonstrated that the phosphodiesterase inhibitor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In each perfusion, samples were taken from the influent and effluent media for measurement of 13 CO 2 release, enzymatic assays, GC (gas chromatography)-MS or LC (liquid chromatography)-MS analyses as indicated [9,10]. At the end of perfusion the liver was freeze-clamped with aluminum tongs pre-cooled in liquid N 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In each perfusion, samples were taken from the influent and effluent media for measurement of 13 CO 2 release, enzymatic assays, GC (gas chromatography)-MS or LC (liquid chromatography)-MS analyses as indicated [9,10]. At the end of perfusion the liver was freeze-clamped with aluminum tongs pre-cooled in liquid N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, an aliquot (500 μ l) of effluent, liver or hepatocyte extracts was purified by passage through an AG-1 column (Cl − : 100–200 mesh; 0.5 cm×2.5 cm) for separation of organic acids and glutamate and aspartate residues or by passage through an AG-50 column (H + : 100–200 mesh) for separation of alanine, serine, glycine and glutamine residues and urea. Then, samples were converted into the t-butyldimethylsilyl derivatives [9,10]. Isotopic enrichment in [ 13 C]alanine isotopomers was monitored using ions at m / z 260, 261, 262 and 263 for M0, M1, M2 or M3 (containing one to three 13 C atoms above M0, the natural abundance) respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IBMX is a competitive phosphodiesterase inhibitor and an adenosine antagonist 39,40 . Nissim et al, demonstrated that IBMX exposure inhibited the mitochondrial respiratory chain and reduced OCR during liver perfusion of rats 41 . 1,3 dimethyl-8-phenyltheophylline is a selective A 1 adenosine receptor antagonist; however, there are no known effects of this compound on mitochondrial function 42 .…”
Section: Discussionmentioning
confidence: 99%